Cross-border ties, nativity, and inflammatory markers in a population-based prospective study of Latino adults. (August 2018) - Torres, Jacqueline M.; Epel, Elissa S.; To, Tu My; Lee, Anne; Aiello, Allison E.; Haan, Mary N.
Abstract: Even after migration, immigrants and their descendants may continue to have ties to family and friends who remain in places of origin. Recent research suggests that these cross-border social ties have implications for health, although this scholarship has been limited to self-reported outcomes. Using data from the Sacramento Area Latino Study on Aging (SALSA), we estimate associations between cross-border social ties and inflammatory biomarkers among Latino adults (n = 1786). We find that immigrants who maintained any cross-border connection to family and friends in Latin America had significantly lower levels of baseline interleukin-6 (IL-6) and C-reactive protein (CRP) compared to their US-born counterparts with no cross-border ties. These results held for values of CRP at five-year follow-up for men only. In contrast, US-born women with cross-border ties to family and friends in Latin America had both significantly higher levels of CRP and significantly lower levels of tumor necrosis factor-alpha (TNF-α) at five-year follow-up relative to their US-born counterparts with no cross-border ties. We find descriptively that men who have cross-border ties are also less likely to be socially isolated within local contexts. Considering place-of-origin social connections may contribute critical nuance to studies of immigrant health, including disparities in inflammatory markers that may serve as indicators of underlying chronic disease. Highlights: We evaluated relationships between cross-border ties (CBT) and inflammation. Data are from a population-based study of immigrant and US-born (USB) Latinos 60+. Immigrants with any CBT had lower baseline IL-6 and CRP than USB with no CBT. This pattern held at 5-year follow-up for models of CRP for men only.